Handcrafted digital light processing apparatus for additively manufacturing oral-prosthesis targeted nano-ceramic resin composites - Yao Lu (De Gruyter, 2021)
3D-printing finds increasing applications including the dental implant. We report in this study a nicely printed and then cured composite consisting of nano-ceramic and photosensitive resin, targeting oral prosthesis application. The results show that the 3D-printed material has good geometry accuracy and satisfactory hardness, justifying its potential as an advanced manufacturing methodology for future dentistry.